IMPRONTAS TEATRALES EN EL CINE ARGENTINO CONTEMPORÁNEO: TRES MODALIDADES DE ASIMILACIÓN - Dra. Carolina SORIA (Fonseca, Journal of Communication, 2023)
At the beginning of the new century, Argentine cinema added to its repertoire topics, narrative and expressive procedures from the theatre of the previous decade. Among the different modalities of assimilation, we can distinguish in first place the films made by stage directors and actors that evidenced the formal concerns and the inquiries of language that come from their theatrical work. In second place, films of the mise-en-scène and «minimal situations» in which there is a revaluation of the image above the actions that develop in its interior, through the predominant use of stylistic resources of clear theatrical imprint such as the long take and the depth of field.